2018
DOI: 10.1002/ajoc.201800285
|View full text |Cite
|
Sign up to set email alerts
|

I2/TBPB Mediated Oxidative Reaction to Construct of Imidazo[1,5‐α]pyridines under Metal‐Free Conditions

Abstract: A new method for the synthesis of imidazo[1,5‐α]pyridines, one of the most important N‐heterocyclic compounds due to their wide application, was reported in this study. Specifically, using I2 as a non‐metal catalyst and TBPB as an oxidant can efficiently facilitate the synthesis and avoid the use of a metal catalyst. The reaction between ethyl (E)‐2‐(benzylideneamino)acetate and pyridine represents an unprecedented 1,3‐diolar cycloaddition in highly straightforward process with great value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…[76] Typically these catalysts require further reagents or co-catalysts such as Lewis acids (BF 3 ), dehydrating agents (e. g. molecular sieves [63] or propane phosphoric acid anhydride [42] ) or oxidant agents (e. g. oxygen, iodine, [72] selenium dioxide, [51] elemental sulphur [76] or tert-butylperoxybenzoate). [75] These problems hindered the practical application of these products and their corresponding transformation or functionalization. Therefore, the development of new strategies under metal-and oxidant-free conditions from readily available materials remains a great challenge to design new luminescent products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[76] Typically these catalysts require further reagents or co-catalysts such as Lewis acids (BF 3 ), dehydrating agents (e. g. molecular sieves [63] or propane phosphoric acid anhydride [42] ) or oxidant agents (e. g. oxygen, iodine, [72] selenium dioxide, [51] elemental sulphur [76] or tert-butylperoxybenzoate). [75] These problems hindered the practical application of these products and their corresponding transformation or functionalization. Therefore, the development of new strategies under metal-and oxidant-free conditions from readily available materials remains a great challenge to design new luminescent products.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year a new and different method for the synthesis of impy was reported (last reaction in Scheme 11). [75] This synthetic approach between ethyl ( E )‐2‐(benzylidene amino)acetate and pyridine employed I 2 as the non‐metal catalyst and tert ‐butylperoxybenzoate as the oxidant. This reaction represents an unprecedented 1,3‐dipolar cycloaddition in a highly straightforward process with great value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, we synthesized ethyl 3-phenylimidazo[1,5a]pyridine-1-carboxylates by the oxidative cyclization of ethyl (E)-2-(benzylideneamino)acetates with pyridines by using I 2 as a catalyst and tert-butyl peroxybenzoate (TBPB) as an oxidant (Scheme 21). 48 This reaction is an extension of that described in Scheme 4, permitting the syntheses of various heterocycles with complementary diversification.…”
Section: Scheme 20mentioning
confidence: 99%
“…Qin et al 45 reported a straightforward method for synthesizing imidazo[1,5- a ]pyridines 120 from ethyl ( E )-2-(benzylideneamino)acetates 118 and pyridines 119 via 1,3-dipolar cycloaddition. Specifically, I 2 was used as a nonmetal catalyst and tert -butyl peroxybenzoate (TBPB) was used as an oxidant to facilitate the synthesis without requiring metal catalysts.…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%